Estimating the Clark Instantaneous Unit Hydrograph Parameters for selected gauged catchments in the west coast of peninsular Malaysia. - Osman, Sazali (Asean Engineering Journal)
Design hydrographs are important for the design of hydraulic structures such as spillways and retention ponds. Due to the lack of the local data, engineers have to estimate design floods based on techniques which are able to predict runoff based on rainfall on a regional basis. In this study, Clark instantaneous unit hydrographs are used to predict design flood hydrographs for the selected catchments in Pulau Pinang, Perak and Selangor. Recorded rainfall and flood events are used to calibrate the parameters of Clark unit hydrograph model, the time of concentration, Tc and storage coefficient, R. The efficiency of the model for the calibrated events was measured by Nash and Sutcliffe method. The efficiency of the model for the calibrated events than 0.91 which show good performance of the model for the calibrated events. The parameters are then related to catchment characteristics such as area, main river length and slope of the catchments. The derivation of the empirical equation of Clark unit hydrograph parameters is desirable to identify the model for ungauged catchments in the region. The validity of the equations was tested by using additional storm events and the results show that equations are performing well using the validation datasets. Results show that the Clark instantaneous unit hydrograph model developed in this study can be an effective tool, predicting a reliable hydrograph within study area even though only limited catchments are used.